Smart Dustbin with Garbage Level Monitoring - Che Mat Salwi, Muhammad Ikmal; Supaiman, Muhammad Syamir; Ainul Jamilus, Mohammad Alif Asraff; Mohd, Mohd Sabani (Multidisciplinary Applied Research and Innovation, 2022)
In this research, the problem of spreading of bacteria and virus upon the contact on the dustbin can be solved by smart dustbin. Apparently, the main objective of this project is to design a prototype of smart dustbin with garbage level monitoring that can solve our problem. In order to create the smart dustbin, we will be used a one dustbin, box 64x43cm and related electronic device that can relate with the Arduino Uno microcontroller. The methodology that is been apply in this project is referring to the System Development Life Cycle (SDLC) which contains of planning, analysis, design, implementation and maintenance. However, there are 4 major steps only selected in order to suite with the project which planning for the data collection of hardware and software, analysis for the analysis of the circuit project, design for mechanical parts, and implementation for testing and troubleshoot of the circuit. The principle of this dustbin is works by the sensor that is sense the object, and let the lid to lift up by using the servo motor. Then, the sensor in dustbin will works as level monitoring to display the percentage left in the dustbin by LCD display. This project used Proteus software in order to do the analysis of Vin and Vout for the circuit. The result in this project is the measurement of the distance that sense from the sensor lid and the measurement sensor from level monitoring.